1998
DOI: 10.1017/s0007485300026067
|View full text |Cite
|
Sign up to set email alerts
|

Flight initiation and flight activity in Prostephanus truncatus (Coleoptera: Bostrichidae)

Abstract: In an outdoor experimental set-up, the number of Prostephanus truncatus (Horn) flying from maize cobs was recorded over 38 observation weeks. Flight activity in the field was recorded for 50 weeks with three pheromone traps, each placed at c. 100-300 m from the first experimental set-up. Multiple regression analyses revealed that both flight initiation and flight activity were partly influenced by mean temperatures, but were not directly related. Flight initiation was mainly dependent on population density. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Similar peaks in catch have been reported previously from Mono province in Benin (Borgemeister et al, 1997b) but not from the coastal zone where there is a single annual rise and fall, presumably because humidities there do not drop below 50% during the period of the Harmattan. In the case of the Benin coastal zone, P. truncatus trap catch was related only to mean temperature (Borgemeister et al, 1997b;Scholz et al, 1998), a finding consistent with the current study in years when humidity is not limiting. The observed response of the beetle to low humidity conditions confirms previous reports.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar peaks in catch have been reported previously from Mono province in Benin (Borgemeister et al, 1997b) but not from the coastal zone where there is a single annual rise and fall, presumably because humidities there do not drop below 50% during the period of the Harmattan. In the case of the Benin coastal zone, P. truncatus trap catch was related only to mean temperature (Borgemeister et al, 1997b;Scholz et al, 1998), a finding consistent with the current study in years when humidity is not limiting. The observed response of the beetle to low humidity conditions confirms previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, it has been shown that there is a significant positive correlation between trap catch and the likelihood that stored food becomes infested (Birkinshaw et al, 2002). This indicates that traps give an effective measure of the dispersing population that threatens stored food, although this population is skewed by sex, because 60-70% is female (Hodges et al, 1998;Scholz et al, 1998), and by age, because young beetles are more likely to fly and are more active fliers (Fadamiro, 1996;Scholz, 1997). However, pheromone traps are expensive and time consuming to deploy so their long-term use by extension services in developing countries is unlikely to be sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…The spread of another Bostrychid, the larger grain borer Prostephanus truncatus, which was accidentally introduced with maize imports to Africa, was also monitored successfully with pheromone traps for enabling better control methods of this invasive species (Richter & Biliwa 1991, Scholz et al 1998. In its native habitats in South-and Central-America like Mexico (Hodges 1986), mark-release-recapture studies revealed maximum natural dispersion capabilities of P. truncatus to be 250 to 340 m in 24 hours depending on the wind speed and direction (Rees et al 1991, Farell & Key 1992.…”
Section: Present Situationmentioning
confidence: 99%
“…Now that P. truncates is present in the African zoogeographic zone it is important to know whether this insect is tight to the post-harvest situation with possible dispersion following grain trade or whether the beetle establishes as a new faunaelement in African forests just like in its Central-American geographic origin. Pheromone-baited trapping of the larger grain borer in forest areas of Benin proved the presence of this pest in natural habitats (Borgemeister et al 1998), indicating its faunistic integration, although the non-agricultural host plants for feeding and breeding are not yet identified (Nansen et al 2002).…”
Section: Present Situationmentioning
confidence: 99%
“…Synthetic pheromone traps catch predominantly young, mated females, though males are also attracted (Scholz et al, 1997a(Scholz et al, ,b 1998a. The proportion of the population of a maize store that disperses is related to population density and the status of the food substrate (Scholz et al, 1998b). Flying adults can be found all year round, but there are strong peaks of flight activity that have been correlated with rainfall and other weather events (Nang'ayo et al, 1993;Borgemeister et al, 1997b;Nansen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%